An Analysis of Thematic Structure Found on Ted Talk You Tube Video - Ningsih, Ni Kadek Gita; Permana, I Putu Andri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 2 (2024): SeptemberDO - 10.24843/ling.2024.v31.i02.p07, 2024)
Thematic progression concerns about the way in which text developed the ideas distributes in a sentence. More specifically thematic progression concerns with relation of theme and rheme of the text. The arrangement of theme and rheme influences the flow of a text or thematic progression which later creates a coherent text. The methodology of this study was qualitative research. The data were in the form of clause. The analysis types of themes in thematic progression based on Halliday (1994) while the analysis of the types of thematic progression was as based on McCabe (1999) added by Abed (2007) theory. The findings of this study indicate that most frequent types of themes and thematic progression patterns are topical theme and constant thematic progression.